Pressure sensitive adhesive sheet
Patent Information
- Application Number
- JP2023119329
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
Smart Images

Figure 2025016202000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive sheet, and more particularly to a pressure-sensitive adhesive sheet capable of exhibiting easy peelability in response to a thermal stimulus. [Background technology]
[0002] Conventionally, adhesive sheets have been used to fix or temporarily fix workpieces when processing electronic components, etc. For example, adhesive sheets are used as temporary fixing materials for cutting semiconductor wafers or ceramic sheets, or as temporary fixing materials in processes for sealing semiconductor chips with resin (chip size package: CSP and wafer level package: WLP). As one such adhesive sheet, an adhesive sheet that has an adhesive layer containing heat-expandable microspheres and whose adhesive strength decreases due to foaming of the heat-expandable microspheres caused by heating has been studied.
[0003] In recent years, in the field of semiconductor packaging for FOWLP, high positional accuracy is required when resin-encapsulating semiconductor chips in order to expand the range of applicable semiconductor devices. The fluidity of the encapsulation resin has a large effect on chip shift during the resin-encapsulation process, and the trend of increasing the resin-encapsulation temperature to improve chip-shift variation is accelerating. If the above-mentioned adhesive sheet is used in such a resin-encapsulation process, the increase in the resin-encapsulation temperature will approach the temperature at which the heat-expandable microspheres expand, causing changes in the thickness of the adhesive sheet and / or the surface roughness of the adhesive sheet, which will cause problems such as worsening chip-shift variation. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-201452 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve the above-mentioned problems in the conventional art, and an object of the present invention is to provide a pressure-sensitive adhesive sheet which contains heat-expandable microspheres and can exhibit peelability upon heating, and which suppresses changes in thickness and surface roughness even at high temperatures where peeling is not required. [Means for solving the problem]
[0006] [1] An adhesive sheet according to one embodiment of the present invention comprises a substrate, a resin layer, and a first adhesive layer in this order, the first adhesive layer containing heat-expandable microspheres, and a thickness deformation onset temperature Tf (°C) of the adhesive sheet as determined by TMA analysis and a gasification onset temperature Tgas (°C) of the heat-expandable microspheres as determined by EGA / MS analysis satisfy the relationship Tf≧Tgas-10. [2] The pressure-sensitive adhesive sheet according to the above item [1] may further include a second pressure-sensitive adhesive layer on the opposite side of the substrate to the resin layer. [3] In the adhesive sheet described in [2] above, the ratio (rate of change) of the surface roughness Ra(II) of the second adhesive layer surface after heating for 450 seconds in an environment at 160°C after storage to the surface roughness Ra(I) of the second adhesive layer surface when the adhesive sheet is heated in an environment at 130°C for 30 minutes and then stored at 25°C / 60%RH for 24 hours may be 130% or less. [4] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [3], the heat-expandable microspheres may have a gasification initiation temperature Tgas of lower than 180°C. [5] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [3], the heat-expandable microspheres may have a gasification initiation temperature Tgas of 180° C. or higher. [6] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [5], the first pressure-sensitive adhesive layer may have a thickness smaller than a thickness of the resin layer. [7] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [6], the volume filling rate of the heat-expandable microspheres in the first pressure-sensitive adhesive layer may be 21% or less. [8] In the pressure-sensitive adhesive sheet according to any one of [1] to [7] above, the resin layer may have a dynamic storage modulus G' at 160° C. of 0.1 MPa or less. [9] In the pressure-sensitive adhesive sheet according to any one of the above [1] to [8], the substrate may have a thickness of 40 μm to 200 μm. Effect of the Invention
[0007] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet which contains heat-expandable microspheres and can exhibit peelability upon heating, and which suppresses changes in thickness and surface roughness even at high temperatures where peeling is not required. [Brief description of the drawings]
[0008] [Figure 1] 1 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] A. Overview of adhesive sheets Fig. 1(a) is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. The pressure-sensitive adhesive sheet 100 comprises, in this order, a substrate 10, a resin layer 20, and a first pressure-sensitive adhesive layer 30. The first pressure-sensitive adhesive layer 30 contains heat-expandable microspheres. As shown in Fig. 1(b), a second pressure-sensitive adhesive layer 40 may be provided on the side of the substrate 10 opposite the resin layer 20.
[0010] The heat-expandable microspheres can be expanded at a predetermined temperature. When the heat-expandable microspheres of the first pressure-sensitive adhesive layer are expanded by heating, unevenness is generated on the adhesive surface (i.e., the surface of the first pressure-sensitive adhesive layer), and the adhesive strength is reduced or lost. When the pressure-sensitive adhesive sheet of the present invention is used as a sheet for temporarily fixing a workpiece during processing of an electronic component (e.g., a semiconductor chip), the adhesive strength required for temporary fixing is exhibited when the workpiece is subjected to a predetermined processing (e.g., resin sealing, etc.), and when the workpiece is peeled off after processing, the adhesive strength is reduced or lost by heating, and good peelability is exhibited.
[0011] In an embodiment of the present invention, the thickness deformation starting temperature Tf (° C.) of the pressure-sensitive adhesive sheet determined by TMA analysis and the gasification starting temperature Tgas (° C.) of the heat-expandable microspheres determined by EGA / MS analysis have the relationship Tf≧Tgas-10.
[0012] The thickness deformation starting temperature Tf by TMA analysis is the temperature at which the thickness of the pressure-sensitive adhesive sheet starts to change due to heating, and is measured from a displacement-temperature curve by TMA analysis. Specifically, in this specification, the thickness deformation starting temperature Tf by TMA analysis is defined as the temperature at which the displacement amount is 15 μm, with the displacement at 40° C. as the reference (0 μm). In one embodiment, the thickness deformation starting temperature Tf by TMA analysis is mainly caused by the change in thickness of the first pressure-sensitive adhesive layer due to the behavior of the heat-expandable microspheres. A method for measuring the thickness deformation starting temperature Tf by TMA analysis will be described later.
[0013] The gasification onset temperature Tgas of heat-expandable microspheres determined by EGA / MS analysis is the temperature at which the heat-expandable microspheres begin to foam when heated. Specifically, in this specification, the gasification onset temperature Tgas of heat-expandable microspheres determined by EGA / MS analysis is defined as the temperature at which the peak at mass m / z=57 in EGA / MS analysis of the pressure-sensitive adhesive sheet is 2% of the maximum gas generation peak intensity.
[0014] In the present invention, by making the thickness deformation start temperature Tf and the gasification start temperature Tgas of the heat-expandable microspheres have the above-mentioned relationship, it is possible to obtain a pressure-sensitive adhesive sheet that exhibits little change in surface state (e.g., change in shape and roughness due to thickness change) at high temperatures that do not require peeling. When such a pressure-sensitive adhesive sheet is used, it is possible to suppress variations in chip shift at high temperatures that do not require peeling when electronic components such as semiconductor chips are temporarily fixed on the pressure-sensitive adhesive sheet. In one embodiment, changes in the surface state of the surface of the pressure-sensitive adhesive sheet opposite to the outer surface of the first pressure-sensitive adhesive layer (e.g., the substrate, the second pressure-sensitive adhesive layer) are suppressed. Preferably, the thickness deformation start temperature Tf (°C) determined by TMA analysis and the gasification start temperature Tgas (°C) of the heat-expandable microspheres determined by EGA / MS analysis have a relationship of Tf≧Tgas-7, preferably a relationship of Tf≧Tgas-5, and more preferably a relationship of Tf≧Tgas-2. If such a relationship is satisfied, the above-mentioned effect becomes remarkable. In one embodiment, the upper limit of Tf is Tgas+15°C.
[0015] In one embodiment, the thickness deformation starting temperature Tf determined by TMA analysis is preferably 140°C to 300°C, and more preferably 160°C to 250°C.
[0016] The adhesive strength at 23°C when the first adhesive layer of the adhesive sheet is attached to polyethylene terephthalate (also referred to as normal adhesive strength X) is preferably 0.5 N / 20mm or more, more preferably 1N / 20mm to 30N / 20mm, even more preferably 2N / 20mm to 20N / 20mm, and even more preferably 3.5N / 20mm to 15N / mm. Within such ranges, an adhesive sheet useful as a temporary fixing sheet used in the manufacture of electronic components can be obtained. In this specification, the adhesive strength refers to the adhesive strength in a state where there is no adhesive strength reduction due to the expansion of the heat-expandable microspheres, and refers to the adhesive strength in a state where there is no thermal history of 40°C or more. The adhesive strength refers to the adhesive strength measured by a method in accordance with JIS Z 0237:2009 (lamination conditions: 1 round trip with a 2 kg roller, peel speed (pulling speed): 300 mm / min, peel angle 180°).
[0017] The adhesive strength of the first adhesive layer of the adhesive sheet when attached to polyethylene terephthalate is preferably reduced by heating to 0.3 N / 20 mm or less (preferably 0.2 N / 20 mm or less, more preferably 0.1 N / 20 mm or less). The heating temperature is preferably 150° C. to 300° C., more preferably 170° C. to 280° C. In one embodiment, the heating temperature may be the gasification initiation temperature Tgas.
[0018] The adhesive strength Y at (gasification start temperature Tgas-10)°C when the first adhesive layer of the above adhesive sheet is attached to polyethylene terephthalate is preferably 0.6 N / 20 mm to 40 N / 20 mm, more preferably 1.5 N / 20 mm to 30 N / 20 mm, and even more preferably 3 N / 20 mm to 20 N / mm.
[0019] The ratio (Y / X) of the adhesive strength Y at (gasification start temperature Tgas-10)°C when the first adhesive layer of the adhesive sheet is attached to polyethylene terephthalate to the normal adhesive strength X of the first adhesive layer is preferably 0.6 or more, more preferably 0.8 or more, and even more preferably 0.9 or more. Within such a range, an adhesive sheet can be obtained that has little change in surface state (e.g., change in shape and change in roughness due to change in thickness) at high temperatures that do not require peeling. In one embodiment, the upper limit of Y / X is 1. In another embodiment, the upper limit of Y / X is 1.2.
[0020] The thickness of the pressure-sensitive adhesive sheet is preferably 10 μm to 400 μm, more preferably 20 μm to 200 μm, and even more preferably 30 μm to 150 μm.
[0021] B. First Adhesive Layer The first pressure-sensitive adhesive layer contains heat-expandable microspheres as described above. The first pressure-sensitive adhesive layer may further contain a pressure-sensitive adhesive.
[0022] Examples of the adhesive constituting the first adhesive layer include acrylic adhesives, rubber adhesives, and silicone adhesives. Among them, acrylic adhesives can be preferably used. In addition, an active energy ray curable acrylic adhesive (hereinafter, active energy ray curable adhesive) may be used as the adhesive. Details of the adhesive are described in, for example, JP 2015-168711 A. The description of this publication is incorporated herein by reference.
[0023] (Acrylic adhesive) In one embodiment, an acrylic adhesive is used as the adhesive. Examples of the acrylic adhesive include an acrylic adhesive having an acrylic polymer (homopolymer or copolymer) using one or more (meth)acrylic acid alkyl esters as a monomer component as a base polymer.
[0024] Specific examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and ) C1-20 alkyl esters of (meth)acrylic acid such as nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, preferred are (meth)acrylic acid alkyl esters having a linear or branched alkyl group having 4 to 20 carbon atoms (more preferably 6 to 20, particularly preferably 8 to 18), and more preferably 2-ethylhexyl (meth)acrylate.
[0025] The acrylic polymer may contain units corresponding to other monomer components copolymerizable with the alkyl (meth)acrylate, if necessary, for the purpose of modifying properties such as cohesive strength, heat resistance, and crosslinkability. Examples of such monomer components include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itanoic anhydride; hydroxyl group-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; sulfonic acid group-containing monomers such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; (N-substituted) amide monomers such as N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; aminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and t-butylaminoethyl(meth)acrylate; alkoxyalkyl(meth)acrylate monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide;succinimide monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinylcaprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and methoxyethyl (meth)acrylate. glycol-based acrylic ester monomers such as ethylene glycol and methoxypolypropylene glycol (meth)acrylate; acrylic ester monomers having a heterocycle, a halogen atom, a silicon atom, or the like, such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, and silicone (meth)acrylate; polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; olefin-based monomers such as isoprene, butadiene, and isobutylene;Examples of the monomer component include vinyl ether monomers such as vinyl ether. These monomer components may be used alone or in combination of two or more. Among the above, more preferred are carboxyl group-containing monomers (particularly preferably acrylic acid) or hydroxyl group-containing monomers (particularly preferably hydroxyethyl (meth)acrylate). The content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.1% by weight to 10% by weight, more preferably 0.5% by weight to 5% by weight, and particularly preferably 1% by weight to 4% by weight, based on the total structural units constituting the acrylic polymer. The content of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.1% by weight to 20% by weight, more preferably 0.5% by weight to 10% by weight, and particularly preferably 1% by weight to 7% by weight, based on the total structural units constituting the acrylic polymer. In this specification, (meth)acrylic means acrylic and / or methacrylic.
[0026] The acrylic adhesive may contain any suitable additives as necessary, such as crosslinkers, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.
[0027] Examples of the crosslinking agent contained in the acrylic adhesive include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred.
[0028] Specific examples of the isocyanate-based crosslinking agent contained in the acrylic pressure-sensitive adhesive include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate; and isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HX"). The content of the isocyanate-based crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.1 to 20 parts by weight, and more preferably 0.5 to 10 parts by weight, per 100 parts by weight of the base polymer.
[0029] Examples of the epoxy crosslinking agent contained in the acrylic pressure-sensitive adhesive include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1500NP"), ), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolight 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolight 70P"), polyethylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol E-400"), polypropylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol P-200"), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, product name "Denacol" Examples of the epoxy crosslinking agent include glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-611"), glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-314"), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-512"), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. The content of the epoxy crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, relative to 100 parts by weight of the base polymer.
[0030] The tackifier contained in the acrylic pressure-sensitive adhesive may be any appropriate tackifier, such as a tackifier resin. Specific examples of the tackifier resin include rosin-based tackifier resins (e.g., unmodified rosin, modified rosin, rosin phenol-based resins, rosin ester-based resins, etc.), terpene-based tackifier resins (e.g., terpene-based resins, terpene phenol-based resins, styrene-modified terpene-based resins, aromatic modified terpene-based resins, hydrogenated terpene-based resins), hydrocarbon-based tackifier resins (e.g., aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins (e.g., styrene-based resins, xylene-based resins, etc.), aliphatic and aromatic petroleum resins, aliphatic and alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone-based resins, coumarone-indene resins, etc.), phenol-based tackifier resins (e.g., alkylphenol-based resins, xylene formaldehyde-based resins, resols, novolacs, etc.), ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, elastomer-based tackifier resins, etc. Among them, rosin-based tackifier resins, terpene-based tackifier resins, or hydrocarbon-based tackifier resins (such as styrene-based resins) are preferred. The tackifiers may be used alone or in combination of two or more. The amount of the tackifier added is preferably 5 to 100 parts by weight, more preferably 10 to 50 parts by weight, based on 100 parts by weight of the base polymer.
[0031] (thermal expandable microspheres) As the heat-expandable microspheres, any suitable heat-expandable microspheres can be used so long as they can expand or foam when heated.Typical heat-expandable microspheres are microspheres in which a substance that gasifies when heated and expands easily is encapsulated in an elastic shell.Such heat-expandable microspheres can be produced by any suitable method, such as a coacervation method or an interfacial polymerization method.
[0032] Examples of substances that gasify and expand easily when heated include liquids such as propane, propylene, butene, normal butane, isobutane, isopentane, neopentane, normal pentane, normal hexane, isohexane, heptane, octane, petroleum ether, methane halides, and tetraalkylsilanes; azodicarbonamide that gasifies by thermal decomposition; and the like.
[0033] Examples of materials constituting the shell include polymers composed of nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and fumaronitrile; carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid; vinylidene chloride; vinyl acetate; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and β-carboxyethyl acrylate; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; and amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide. Polymers composed of these monomers may be homopolymers or copolymers. Examples of such copolymers include vinylidene chloride-methyl methacrylate-acrylonitrile copolymer, methyl methacrylate-acrylonitrile-methacrylonitrile copolymer, methyl methacrylate-acrylonitrile copolymer, acrylonitrile-methacrylonitrile-itaconic acid copolymer, and the like.
[0034] In one embodiment, a liquid containing isooctane is used as the substance that gasifies and expands easily when heated. The liquid containing isooctane may contain other liquids (e.g., isopentane, n-octane). By using a liquid containing isooctane, a first pressure-sensitive adhesive layer having a high gasification start temperature Tgas of the heat-expandable microspheres (e.g., 180°C or higher) and excellent heat resistance can be formed, and a pressure-sensitive adhesive sheet with little change in surface state (e.g., change in shape and change in roughness due to change in thickness) can be easily obtained at high temperatures that do not require peeling.
[0035] The gasification onset temperature Tgas of the heat-expandable microspheres is preferably 140° C. to 250° C., more preferably 150° C. to 240° C., and further preferably 160° C. to 230° C. The gasification onset temperature Tgas of the heat-expandable microspheres can be adjusted by the boiling point of the substance (liquid) that easily expands when heated, the composition of the substance (liquid) that easily expands when heated (e.g., the mixing ratio of different types of substances (liquids)), the composition of the polymer constituting the shell, the glass transition temperature of the polymer constituting the shell, the molecular weight of the polymer constituting the shell, the thickness of the shell, etc.
[0036] In one embodiment, the gasification onset temperature Tgas of the heat-expandable microspheres is less than 180°C.
[0037] In another embodiment, the gasification onset temperature Tgas of the heat-expandable microspheres is equal to or higher than 180° C. If Tgas is within this range, a first pressure-sensitive adhesive layer having excellent heat resistance can be formed, and a pressure-sensitive adhesive sheet with minimal changes in surface condition (e.g., changes in shape and roughness associated with changes in thickness) can be easily obtained at high temperatures that do not require peeling.
[0038] The particle size of the heat-expandable microspheres before heating is preferably 0.5 μm to 80 μm, more preferably 5 μm to 45 μm, further preferably 10 μm to 20 μm, and particularly preferably 10 μm to 15 μm. Thus, the particle size of the heat-expandable microspheres before heating, expressed in terms of average particle size, is preferably 6 μm to 45 μm, more preferably 15 μm to 35 μm. The particle size and average particle size are values determined by a particle size distribution measurement method using a laser scattering method.
[0039] The heat-expandable microspheres preferably have an appropriate strength so that they do not burst until their volumetric expansion rate reaches at least 5 times, more preferably at least 7 times, and even more preferably at least 10 times. When such heat-expandable microspheres are used, their adhesive strength can be efficiently reduced by heat treatment.
[0040] The content of the heat-expandable microspheres in the first pressure-sensitive adhesive layer can be appropriately set depending on the desired decrease in adhesive strength, etc. The content of the heat-expandable microspheres is, for example, 1 to 150 parts by weight, preferably 10 to 130 parts by weight, and more preferably 15 to 100 parts by weight, relative to 100 parts by weight of the base polymer forming the first pressure-sensitive adhesive layer.
[0041] The volumetric filling rate of the heat-expandable microspheres in the first pressure-sensitive adhesive layer is preferably 28% or less, more preferably 24% or less, and even more preferably 21% or less. Within such a range, a pressure-sensitive adhesive sheet can be obtained that undergoes minimal changes in surface condition (e.g., changes in shape and roughness associated with changes in thickness) at high temperatures that do not require peeling. In one embodiment, changes in the surface condition of the surface of the pressure-sensitive adhesive sheet opposite to the outer surface of the first pressure-sensitive adhesive layer (e.g., the substrate, the second pressure-sensitive adhesive layer) are suppressed. The effect of setting the volumetric filling rate of the heat-expandable microspheres within the above range is particularly effective when the gasification initiation temperature Tgas of the heat-expandable microspheres is less than 180°C. The volumetric filling rate of the heat-expandable microspheres in the first pressure-sensitive adhesive layer is preferably 10% or more, and more preferably 15% or more.
[0042] The arithmetic surface roughness Ra of the first pressure-sensitive adhesive layer before the heat-expandable microspheres expand (i.e., before heating) is preferably 500 nm or less, more preferably 400 nm or less, and further preferably 300 nm or less. The arithmetic surface roughness Ra can be measured in accordance with JIS B 0601.
[0043] The thickness of the first pressure-sensitive adhesive layer is preferably 5 μm to 70 μm, more preferably 10 μm to 60 μm, even more preferably 10 μm to 50 μm, and most preferably 10 μm to 40 μm. Within this range, a pressure-sensitive adhesive sheet excellent in operability in liner peeling, operability in application, adhesiveness, smoothness, and deformability upon heating can be obtained. In one embodiment, the thickness of the first pressure-sensitive adhesive layer is 20 μm or less. Within this range, a pressure-sensitive adhesive sheet with small changes in surface state (e.g., changes in shape and roughness associated with changes in thickness) can be obtained at high temperatures that do not require peeling. In one embodiment, changes in the surface state of the pressure-sensitive adhesive sheet on the side opposite to the outer surface of the first pressure-sensitive adhesive layer (e.g., substrate, second pressure-sensitive adhesive layer) are suppressed. This effect is particularly effective when the gasification initiation temperature Tgas of the heat-expandable microspheres is less than 180° C.
[0044] The thickness of the first pressure-sensitive adhesive layer is preferably thinner than that of the resin layer. By adjusting the thicknesses of both layers in this way, a pressure-sensitive adhesive sheet can be obtained that undergoes little change in surface state (e.g., change in shape and change in roughness due to change in thickness) at high temperatures that do not require peeling. In one embodiment, changes in the surface state of the surface of the pressure-sensitive adhesive sheet opposite to the outer surface of the first pressure-sensitive adhesive layer (e.g., the substrate, the second pressure-sensitive adhesive layer) are suppressed. The effect of setting the volumetric filling rate of the heat-expandable microspheres within the above range is particularly effective when the gasification starting temperature Tgas of the heat-expandable microspheres is less than 180°C. The difference between the thickness of the first pressure-sensitive adhesive layer and the thickness of the resin layer is preferably 5 μm or more, more preferably 6 μm to 40 μm, and even more preferably 8 μm to 30 μm.
[0045] The elastic modulus of the first adhesive layer measured by nanoindentation at 25°C is preferably less than 100 MPa, more preferably 0.1 MPa to 50 MPa, and even more preferably 0.1 MPa to 10 MPa. Within such a range, an adhesive sheet having an appropriate adhesive strength can be obtained. The elastic modulus measured by nanoindentation refers to an elastic modulus obtained by continuously measuring the load and indentation depth on an indenter when the indenter is pressed into a sample, during loading and unloading, and then obtaining a load-indentation depth curve. In this specification, the elastic modulus measured by nanoindentation refers to an elastic modulus measured by a single indentation method at a predetermined temperature (25°C) using a nanoindenter (e.g., Triboindenter TI-950 manufactured by Hysitron Inc.) under the measurement conditions of an indentation speed of about 500 nm / sec, an extraction speed of about 500 nm / sec, and an indentation depth of about 3000 nm.
[0046] C. Base material The substrate may be made of any suitable material. As the substrate, various sheet-like materials such as paper, cloth, nonwoven fabric, metal foil, plastic laminates thereof, and laminates of plastics can be used. Among them, plastic films and plastic sheets (hereinafter referred to as plastic films) are most preferable from the viewpoint of handling and cost. The material of the plastic film can be selected as necessary from the viewpoint of strength, heat resistance, and the like. For example, olefin-based resins having α-olefin as a monomer component such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); polyvinyl chloride (PVC); polyphenylene sulfide (PPS); amide-based resins such as polyamide (nylon) and fully aromatic polyamide (aramid); polyether ether ketone (PEEK), polyimide, polyetherimide, polystyrene, and acrylic resins can be mentioned. These materials can be used alone or in combination of two or more. The plastic film may be any of an unstretched film, a uniaxially oriented film, and a biaxially oriented film. These films may be laminated films consisting of two or more film layers, or from the viewpoint of handling, a film containing a lubricant such as inert particles may be appropriately added.
[0047] The thickness of the substrate is preferably 200 μm or less, more preferably 1 μm to 200 μm, further preferably 5 μm to 200 μm, particularly preferably 10 μm to 200 μm, particularly preferably 20 μm to 200 μm, and most preferably 30 μm to 200 μm. If the thickness is within such a range, it can contribute to improving the liner releasability, and a substrate excellent in strength, flexibility, suppleness, buckling resistance, etc. can be obtained.
[0048] In one embodiment, the thickness of the substrate is 40 μm to 200 μm. Within this range, a pressure-sensitive adhesive sheet can be obtained that undergoes minimal changes in surface condition (e.g., changes in shape and roughness associated with changes in thickness) at high temperatures that do not require peeling. In one embodiment, changes in the surface condition of the surface of the pressure-sensitive adhesive sheet opposite the outer surface of the first pressure-sensitive adhesive layer (e.g., substrate, second pressure-sensitive adhesive layer) are suppressed. This effect is particularly effective when the gasification initiation temperature Tgas of the heat-expandable microspheres is lower than 180° C.
[0049] The ratio (rate of change) of the surface roughness Ra(ii) of the second adhesive layer surface after heating for 450 seconds in an environment of 160° C. to the surface roughness Ra(i) of the second adhesive layer surface when the first adhesive sheet is heated in an environment of 130° C. for 30 minutes and then stored at 25° C. / 60% RH for 24 hours is preferably 130% or less, more preferably 101% to 128%, and even more preferably 102% to 120%. Within such a range, a pressure-sensitive adhesive sheet can be obtained in which the shape change of the side opposite to the first adhesive layer is small in an environment not requiring peeling, and the variation in tip shift can be preferably suppressed.
[0050] The elastic modulus of the above-mentioned substrate as measured by a nanoindentation method at 25° C. is preferably 500 MPa to 5000 MPa, more preferably 500 MPa to 4000 MPa, and further preferably 700 MPa to 4000 MPa.
[0051] The substrate may be subjected to a surface treatment, such as corona treatment, chromate treatment, ozone exposure, flame exposure, high-voltage shock exposure, ionizing radiation treatment, or coating with a primer.
[0052] D.Resin layer As described above, the pressure-sensitive adhesive sheet further comprises a resin layer disposed between the first pressure-sensitive adhesive layer and the substrate. The resin layer allows the production of a pressure-sensitive adhesive sheet with excellent conformability to the adherend. When the pressure-sensitive adhesive layer containing heat-expandable microspheres is heated, the heat-expandable microspheres expand and deform in the thickness direction, but the resin layer suppresses deformation in the direction of the substrate, improving peelability. Furthermore, by suitably adjusting the properties of the resin layer (for example, by increasing flexibility), a pressure-sensitive adhesive sheet with small changes in surface state (for example, changes in shape and roughness associated with changes in thickness) can be obtained at high temperatures where peeling is not required. In one embodiment, changes in the surface state of the surface of the pressure-sensitive adhesive sheet opposite to the outer surface of the pressure-sensitive adhesive layer (for example, the substrate, the second pressure-sensitive adhesive layer) are suppressed.
[0053] In one embodiment, the resin layer may contain any appropriate adhesive. Examples of the adhesive constituting the resin layer include acrylic adhesives, rubber adhesives, and silicone adhesives. Among them, acrylic adhesives may be preferably used. Furthermore, an active energy ray curable acrylic adhesive (hereinafter, active energy ray curable adhesive) may be used as the adhesive. Preferably, the adhesive constituting the resin layer is the same as the adhesive constituting the first adhesive layer.
[0054] The thickness of the resin layer is preferably 1 μm to 60 μm, more preferably 5 μm to 50 μm, and further preferably 10 μm to 40 μm. In one embodiment, the thickness of the resin layer is 20 μm or more (preferably 25 μm or more). Within this range, a pressure-sensitive adhesive sheet can be obtained that undergoes little change in surface condition (e.g., change in shape and change in roughness associated with change in thickness) at high temperatures that do not require peeling. In one embodiment, changes in the surface condition of the surface of the pressure-sensitive adhesive sheet opposite to the outer surface of the first pressure-sensitive adhesive layer (e.g., the substrate, the second pressure-sensitive adhesive layer) are suppressed. This effect is particularly effective when the gasification initiation temperature Tgas of the heat-expandable microspheres is lower than 180° C.
[0055] The elastic modulus of the resin layer measured at 25° C. by a nanoindentation method is preferably 0.001 MPa to 10 MPa, more preferably 0.01 MPa to 8 MPa, and more preferably 0.5 MPa to 5 MPa.
[0056] The dynamic storage modulus G' of the resin layer at 160°C is preferably 0.5 MPa or less, more preferably 0.2 MPa or less, and even more preferably 0.1 MPa or less. A pressure-sensitive adhesive sheet with small changes in surface state (e.g., changes in shape and roughness due to changes in thickness) can be obtained at high temperatures that do not require peeling. In one embodiment, changes in the surface state of the surface of the pressure-sensitive adhesive sheet opposite to the outer surface of the first pressure-sensitive adhesive layer (e.g., the substrate, the second pressure-sensitive adhesive layer) are suppressed. This effect is particularly effective when the gasification start temperature Tgas of the heat-expandable microspheres is less than 180°C. The lower limit of the dynamic storage modulus G' of the resin layer at 160°C is, for example, 0.01 MPa. The storage modulus can be measured using a dynamic viscoelasticity measuring device (e.g., "ARES-G2" manufactured by TA instruments) under measurement conditions of a frequency of 1 Hz and a heating rate of 5°C / min.
[0057] E. Second Adhesive Layer Examples of the adhesive constituting the first adhesive layer include acrylic adhesives, rubber adhesives, and silicone adhesives. Among them, acrylic adhesives can be preferably used. In addition, an active energy ray curable acrylic adhesive (hereinafter, active energy ray curable adhesive) may be used as the adhesive. Details of the adhesive are described in, for example, JP 2015-168711 A. The description of this publication is incorporated herein by reference. In one embodiment, the second adhesive layer includes the acrylic adhesive described in Section B. As described above, the acrylic adhesive includes an acrylic polymer as a base polymer.
[0058] The thickness of the second pressure-sensitive adhesive layer is preferably 1 μm to 50 μm, more preferably 2 μm to 60 μm, even more preferably 3 μm to 35 μm, and most preferably 5 μm to 35 μm. Within such a range, a pressure-sensitive adhesive sheet excellent in operability when peeling off the liner, operability when applying, adhesiveness, and smoothness can be obtained. In addition, a pressure-sensitive adhesive sheet with little change in surface state (for example, change in shape and change in roughness due to change in thickness) can be obtained under high temperatures that do not require peeling.
[0059] The second pressure-sensitive adhesive layer preferably has a modulus of elasticity measured by a nanoindentation method at 25° C. of 0.001 MPa to 10 MPa, more preferably 0.01 MPa to 8 MPa. Within such a range, a pressure-sensitive adhesive sheet having excellent operability, adhesiveness, and smoothness when applied can be obtained.
[0060] The ratio (rate of change) of the surface roughness Ra(II) of the second adhesive layer surface after heating for 450 seconds in a 160°C environment to the surface roughness Ra(I) of the second adhesive layer surface when the pressure-sensitive adhesive sheet having the second pressure-sensitive adhesive layer is heated in a 130°C environment for 30 minutes and then stored at 25°C / 60%RH for 24 hours is preferably 130% or less, more preferably 101% to 128%, and even more preferably 102% to 120%. Within such a range, a pressure-sensitive adhesive sheet can be obtained that exhibits small changes in the shape of the second adhesive layer surface and can favorably suppress variations in tip shift in an environment that does not require peeling. Heating and storage during Ra(I) measurement can be performed with a SUS plate attached to the surface of the second adhesive layer.
[0061] F. Manufacturing method of adhesive sheet The pressure-sensitive adhesive sheet can be produced by any suitable method. Examples of the method for producing a pressure-sensitive adhesive sheet include a method of directly coating a resin layer-forming composition on a substrate to form a resin layer, and coating a first pressure-sensitive adhesive layer-forming composition (adhesive + heat-expandable microspheres) on the resin layer, or a method of coating a first pressure-sensitive adhesive layer-forming composition on any suitable substrate to form a coating layer, and transferring the formed coating layer to a substrate / resin layer laminate. When the pressure-sensitive adhesive sheet includes the second pressure-sensitive adhesive layer, the second pressure-sensitive adhesive layer can be formed by coating a second pressure-sensitive adhesive layer-forming composition (adhesive) on the surface of the substrate opposite to the resin layer.
[0062] Examples of the coating method of each of the above compositions include coating methods using a die coater, a comma coater, a gravure coater, etc. As a drying method, heat drying is preferably adopted. For example, drying can be performed by placing the pressure-sensitive adhesive coating layer for a desired time in a dryer equipped with a blower that can forcibly circulate air at a predetermined temperature.
[0063] The drying temperature is preferably 55° C. or higher and lower than 100° C., more preferably 60° C. to 90° C., and further preferably 65° C. to 90° C. The drying time can be any appropriate time. The drying time is, for example, 1 minute to 10 minutes. Within this range, the pressure-sensitive adhesive layer and the like can be formed efficiently.
[0064] G.Applications The pressure-sensitive adhesive sheet can be preferably used as a temporary fixing sheet when processing any appropriate member (for example, electronic components such as semiconductor chips). In one embodiment, the pressure-sensitive adhesive sheet can be used as a temporary fixing sheet in the field of semiconductor packaging of FOWLP (Fan Out Wafer Level Package). In one embodiment, a plurality of semiconductor chips can be arranged as workpieces on the surface of the pressure-sensitive adhesive sheet opposite to the first pressure-sensitive adhesive layer (for example, the second pressure-sensitive adhesive layer surface). The pressure-sensitive adhesive sheet on which the semiconductor chips are arranged is subjected to a predetermined resin sealing process. Even when the pressure-sensitive adhesive sheet is subjected to high temperatures in the resin sealing process, the surface shape is unlikely to change (shape change due to thickness change, change in surface roughness, etc.), making it possible to reduce variations in chip shift of the semiconductor chip. EXAMPLES
[0065] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0066] [Production Example 1] Production of Base Polymer 1 30 parts by weight of 2-ethylhexyl acrylate (EHA), 70 parts by weight of ethyl acrylate (EA), 5 parts by weight of methyl methacrylate (MMA), and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) were added to a toluene solvent, and 0.5 parts by weight of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name: Perbutyl O (registered trademark)) was further added as a polymerization initiator. The mixture was stirred at 80 to 90°C for 12 hours to obtain a toluene solution of polymer 1 with a solid concentration of 40%.
[0067] [Production Example 2] Production of adhesive layer-forming composition 1 (adhesive + heat-expandable microspheres) A toluene solution of polymer 1 (polymer 1:100 parts by weight), 1.4 parts by weight of an isocyanate crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D101A"), 10 parts by weight of a tackifier resin (manufactured by Sumitomo Bakelite Co., Ltd., product name "SUMILITE PR12603"), 30 parts by weight of thermally expandable microspheres (manufactured by Sekisui Chemical Co., Ltd., product name "Advancell EM504", average particle size: 19 μm), and 0.05 parts of dioctyltin dilaurate were mixed to prepare a composition for forming an adhesive layer 1.
[0068] [Production Examples 3 to 7] Production of Pressure-Sensitive Adhesive Layer-Forming Compositions 2 to 6 Compositions 2 to 6 for forming an adhesive layer were produced in the same manner as in Production Example 2, except that the types and amounts of heat-expandable microspheres were as shown in Table 1. <Thermally expandable microspheres> F-230D: Matsumoto Yushi Pharmaceutical Co., Ltd., product name "Matsumoto Microsphere F-230D", average particle size: 23 μm F-2800D: Matsumoto Yushi Pharmaceutical Co., Ltd., product name "Matsumoto Microsphere F-2800D", average particle size: 28 μm
[0069] [Table 1]
[0070] [Production Example 8] Production of resin layer-forming composition 1 A toluene solution of polymer 1 (polymer 1: 100 parts by weight) and 3 parts by weight of an isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D101A") were mixed to prepare a resin layer-forming composition 1.
[0071] [Production Example 9] Production of resin layer-forming composition 2 A resin layer-forming composition 2 was prepared in the same manner as in Production Example 9, except that the amount of the isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D101A") was 1 part by weight.
[0072] [Production Example 10] Production of Adhesive 7 Adhesive 7 was prepared by mixing a toluene solution of polymer 1 (polymer 1:100 parts by weight), 1.5 parts by weight of an isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D101A"), 5 parts by weight of a tackifier resin (manufactured by Sumitomo Bakelite Co., Ltd., product name "Sumilite PR12603"), and 0.05 parts of dioctyltin dilaurate.
[0073] [Example 1] (Preparation of resin layer / substrate laminate) The resin layer-forming composition 1 was applied to one surface of a PET substrate (thickness: 38 μm) using an applicator so that the thickness after solvent evaporation (drying) was 13 μm. Thereafter, the solvent was evaporated (dried) at 150° C. for 1 minute using a forced convection hot air drying oven to obtain a resin layer / substrate laminate. (Preparation of MRF38 (liner) / first adhesive layer (containing heat-expandable microspheres) laminate) The above-mentioned adhesive layer-forming composition 1 was applied to the release agent-coated surface of a liner (PET film, manufactured by Mitsubishi Plastics, Inc., product name "MRF-38") coated with a silicone-based release agent, so that the thickness after solvent evaporation (drying) would be 20 μm. Thereafter, the solvent was evaporated (dried) at 65° C. for 5 minutes using a forced convection hot air drying oven, to obtain an MRF38 (liner) / first adhesive layer (containing heat-expandable microspheres) laminate. (Preparation of MRF38 (liner) / first adhesive layer (containing heat-expandable microspheres) / resin layer / substrate laminate) The MRF38 (liner) / first pressure-sensitive adhesive layer (containing heat-expandable microspheres) and the resin layer / substrate laminate were bonded together so that the first pressure-sensitive adhesive layer (containing heat-expandable microspheres) and the resin layer faced each other to obtain an MRF38 (liner) / pressure-sensitive adhesive layer (containing heat-expandable microspheres) / resin layer / substrate laminate. (Preparation of MRF50 (liner) / second adhesive layer laminate) The pressure-sensitive adhesive 7 was applied to the release-treated surface of a liner (PET film, manufactured by Mitsubishi Plastics, Inc., product name "MRF-38") coated with a silicone-based release agent, so that the thickness after solvent evaporation (drying) would be 5 μm. Thereafter, the solvent was evaporated (dried) at 150°C for 1 minute using a forced convection hot air drying oven, to obtain an MRF50 (liner) / second pressure-sensitive adhesive layer laminate. (Preparation of adhesive sheet with liner) An MRF38 (liner) / first adhesive layer (containing heat-expandable microspheres) / resin layer / substrate laminate and an MRF50 (liner) / second adhesive layer laminate were bonded together with the substrate and the second adhesive layer facing each other to obtain a liner-attached adhesive sheet (MRF38 (liner) / first adhesive layer (containing heat-expandable microspheres) / resin layer / substrate / second adhesive layer / MRF50 (liner)).
[0074] [Examples 2 to 9, Comparative Examples 1 to 3] A liner-attached adhesive sheet was obtained in the same manner as in Example 1, except that the adhesive layer-forming composition used to form the first adhesive layer, the thickness of the first adhesive layer, the resin layer-forming composition used to form the resin layer, the thickness of the resin layer, and the thickness of the substrate were as shown in Table 2 or Table 3.
[0075] <Evaluation> After peeling the liners from the liner-attached PSA sheets obtained in the Examples and Comparative Examples, the PSA sheets were subjected to the following evaluations. The results are shown in Tables 2 and 3.
[0076] (1) Volume filling rate of heat-expandable microspheres i) The sample was fixed to a holder with the first adhesive layer of the adhesive sheet before heating facing up, and 1601 continuous transmission images were taken from 0 to 180° using an X-ray CT. The X-ray CT was performed using a ZEISS Xradia 520 Versa with a tube voltage of 40 kV, a tube current of 73 μA, and a pixel size of 0.3 μm / Pixel. ii) Based on the total transmission image obtained, reconstruction was performed to create a tomographic image, and a three-dimensional reconstruction image (TIF stack image) and a reconstructed cross-sectional image (three-plane view) were created using the analysis software ImageJ. iii) The obtained three-dimensional reconstructed images (TIF stack images) were subjected to image processing to identify the heat-expandable microspheres. From the identification results, the volume filling rate in the thickness direction was calculated. The thickness of the pressure-sensitive adhesive layer of each sample was measured by cross-sectional observation using an SEM, and the filling rate was calculated as the total volume excluding the air bubbles. (2) Gasification start temperature of heat-expandable microspheres, Tgas Approximately 0.5 mg of the adhesive sheet sample was placed in a heating furnace pyrolyzer, and a mass chromatogram was obtained by EGA-MS analysis, which involves mass spectrometry of the components volatilized by heating. The temperature was raised from 40°C to 500°C at a heating rate of 10°C / min using a heating furnace pyrolyzer (manufactured by Frontier Labs, product name "PY2020iD"), and the maximum gas generation peak intensity was measured from the mass chromatogram of mass m / z = 57 using a GC / MS analyzer (manufactured by JEOL, product name "JMS-T100GCV"). The gasification start temperature is defined as the temperature at which the peak intensity of the maximum gas generation peak of the EGA / MS chromatogram obtained from the EGA analysis reaches 2%. (3)Normal adhesion X The adhesive sheets obtained in the examples and comparative examples were cut to a size of 20 mm in width and 140 mm in length. A polyethylene terephthalate film (product name "Lumirror S-10" manufactured by Toray Industries, Inc.; thickness: 25 μm, width: 30 mm) was attached as an adherend to the first adhesive layer side of the adhesive sheet, with 5 mm protruding on both the left and right in the width direction, by rolling a 2 kg roller back and forth once in accordance with JIS Z 0237:2009. The second adhesive layer side was attached to a metal plate (SUS304 plate, thickness 3 mm) via double-sided tape (manufactured by Nitto Denko Corporation, product name "No. 500") to prepare a measurement sample. The load was then measured when the adherend was peeled off from the adhesive sheet in the length direction under the conditions of a peel angle of 180° and a peel speed (tensile speed) of 300 mm / min, the maximum load (maximum load excluding the peak top at the beginning of the measurement) was calculated, and the maximum load was divided by the tape width to obtain the adhesive strength (N / 20 mm width). The above operation was performed in an atmosphere at a temperature of 23°C.
[0077] (4)(Tgas-10)℃ Adhesive strength Y after heating The adhesive strength at (Tgas-10)°C was measured according to the method of (1) above.
[0078] (5)(Tgas+15)℃ Adhesive strength after heating The adhesive strength at (Tgas+15)° C. was measured according to the method of (1) above.
[0079] (6) Storage modulus of resin layer A dynamic viscoelasticity measuring device (manufactured by TA instruments, product name "ARES-G2") was used to measure the storage modulus G' at a measurement frequency of 1 Hz, a strain of 0.05%, and 160° C. Specifically, the measurement was performed by the following method. A resin layer of 50 μm thickness was formed using the same resin layer as that used in each Example and Comparative Example, and the resin layer was laminated to obtain a sample of 1 mm or more in thickness. The obtained sample was punched out to a size of φ8 mm and set on the probe of "ARES-G2". The temperature was raised from -50°C to 260°C at a heating rate of 5°C / min, and the value of the storage modulus G' at 160°C was obtained.
[0080] (7) Thickness deformation start temperature Tf by TMA analysis Using a TMA Q400 (manufactured by TA-instrument), a Φ3.0mm probe was used to measure the displacement-temperature curve of the adhesive sheet in magnification mode under the following conditions: nitrogen gas flow rate: 50.0ml / min, indentation load: 0.0196N, measurement temperature range: 40°C to 260°C, and temperature rise rate: 5°C / min. The thickness deformation start temperature Tf by TMA analysis is defined as the temperature at which the displacement amount becomes 15μm, with the displacement at 40°C as the reference (0μm). Measurements were performed with N=5, and the average value of N=3 excluding the maximum and minimum values among these measured values was taken as the thickness deformation start temperature Tf of the sample.
[0081] (8) Chip shift variation The first adhesive layer of the adhesive sheet obtained in the examples and comparative examples was attached to a SUS substrate (thickness 0.8 mm, diameter 12 inches) using a laminator. In the attachment, the attachment speed was 0.5 m / min, the temperature condition was normal temperature, and the pressure condition was 0.3 MPa. Next, 25 silicon chips (thickness 400 μm, 7 mm square) were radially arranged on the adhesive sheet, 8 pieces each at positions 25 mm, 50 mm, and 100 mm from the center chip, and the pressure was 0.2 MPa. The attachment was performed for 1.0 seconds. Next, the initial position of each chip on the adhesive sheet was measured by observing using a CNC (Computer Numerical Control) image measuring machine (product name "Quickvision PRO", manufactured by Mitutoyo Corporation). Next, the SUS substrate with the silicon chip attached on the adhesive sheet was preheated in a dryer at 130 ° C for 30 minutes, and then stored in a thermo-hygrostat set to 25 ° C / 60% RH for 24 hours. The obtained sample was set in a compression molding device (manufactured by TOWA, product name "CPM1080") and resin-sealed using a sealing resin (manufactured by Sumitomo Bakelite, product name "Sumikon EME-G750") at a sealing temperature of 160°C, a pressure of 50 tons, and a sealing time of 450 seconds. Next, the sample after resin sealing was heated at 200 to 240°C for 5 minutes using a drying oven to reduce the adhesive force of the first adhesive layer (heat-foaming adhesive layer) of the adhesive sheet, and the adhesive sheet and the sealing resin substrate were heated and peeled off from the SUS substrate. Furthermore, the sealing resin substrate was heated on a hot plate preheated to 150°C, and the second adhesive layer of the adhesive sheet was peeled off. The obtained sealing resin substrate was observed using a CNC image measuring device (product name "Quickvision PRO", manufactured by Mitutoyo Corporation), and the position of each chip in the sealing resin substrate after sealing was measured. Based on the obtained silicon chip position information, the relative distance from the center chip to each chip in the initial position and the position after sealing was calculated, and the change in relative distance from the initial position to the position after sealing (chip shift) was measured. The maximum and minimum chip shift values were read for eight silicon chips placed 100 mm away from the center chip, and the difference between them was defined as the chip shift variation.
[0082] [Table 2]
[0083] [Table 3] [Explanation of symbols]
[0084] 10 Base material 20 Resin layer 30 First adhesive layer 40 Second adhesive layer 100, 200 Adhesive Sheet
Claims
1. A pressure-sensitive adhesive sheet comprising a substrate, a resin layer, and a first pressure-sensitive adhesive layer in this order, the first pressure-sensitive adhesive layer contains heat-expandable microspheres, the thickness deformation starting temperature Tf (°C) of the pressure-sensitive adhesive sheet as determined by TMA analysis and the gasification starting temperature Tgas (°C) of the heat-expandable microspheres as determined by EGA / MS analysis satisfy the relationship Tf≧Tgas-10; Adhesive sheet.
2. The pressure-sensitive adhesive sheet according to claim 1 , further comprising a second pressure-sensitive adhesive layer on the opposite side of the substrate to the resin layer.
3. 3. The pressure-sensitive adhesive sheet according to claim 2, wherein the ratio (rate of change) of the surface roughness Ra(II) of the second adhesive layer surface after heating for 450 seconds in an environment at 160°C after storage to the surface roughness Ra(I) of the second adhesive layer surface when the pressure-sensitive adhesive sheet is heated in an environment at 130°C for 30 minutes and then stored at 25°C / 60% RH for 24 hours is 130% or less.
4. The pressure-sensitive adhesive sheet according to claim 1 , wherein the heat-expandable microspheres have a gasification initiation temperature Tgas of less than 180° C.
5. The pressure-sensitive adhesive sheet according to claim 1 , wherein the heat-expandable microspheres have a gasification initiation temperature Tgas of 180° C. or higher.
6. The pressure-sensitive adhesive sheet according to claim 1 , wherein the first pressure-sensitive adhesive layer has a thickness smaller than a thickness of the resin layer.
7. The pressure-sensitive adhesive sheet according to claim 1 , wherein a volume filling rate of the heat-expandable microspheres in the first pressure-sensitive adhesive layer is 21% or less.
8. The pressure-sensitive adhesive sheet according to claim 1, wherein the resin layer has a dynamic storage modulus G' at 160° C. of 0.1 MPa or less.
9. The pressure-sensitive adhesive sheet according to claim 1, wherein the substrate has a thickness of 40 μm to 200 μm.
Citation Information
Patent Citations
Method of manufacturing semiconductor device and adhesive sheet to be used therefor
JP2006295030A
Heating peeling off type adhesive sheet and manufacturing method for chip part
JP2007238789A
Heat-peelable adhesive sheet
JP2008297412A
Sheet-like sealant
JP2015214622A
Pressure sensitive adhesive sheet
JP2018009050A
Cited By
Method of manufacturing electronic devices
JP7911191B1
Method for manufacturing electronic device
WO2026204835A1